Analisis Reflektif Evaluasi Diri Guru Madrasah dalam Implementasi Kurikulum Merdeka Berbasis Temuan Tantangan dan Implikasi Pendampingan - Yasiman, Yasiman; Dodo (urn:issn:2986-9994:sib-v3-i1-20255)
This study aims to analyze the results of teachers’ self-reflective evaluation in the implementation of the Merdeka Curriculum by highlighting achievements, challenges, and mentoring needs. A descriptive qualitative design was employed, with primary data derived from the July teachers’ self-evaluation instrument covering five main aspects: lesson planning, teaching implementation, learning assessment, student guidance, and additional tasks. The findings indicate that most teachers achieved the “target met” category, particularly in planning and student guidance, although a considerable proportion reported “partially implemented” in teaching and assessment. The main challenges include limited ICT resources, low students’ basic literacy, dense learning materials with restricted time allocation, and heavy administrative workload. These findings suggest that teacher reflection is not merely an administrative formality, but an early diagnostic tool that effectively maps teachers’ actual needs. Theoretically, this study contributes by reinforcing the concept of periodic reflection as a strategy for improving teaching quality, while practically it provides recommendations for contextual mentoring by school principals and supervisors. The implications highlight the importance of fostering a reflective, collaborative, and adaptive culture in madrasahs to support the success of the Merdeka Curriculum, with the limitation that classroom observations were not conducted for data triangulation.